Urinary Stents Current State and Future Perspectives - Soria, Federico; Rako, Duje; de Graaf, Petra (Springer Nature, 2022)
This open access book provides a concise overview of a range of aspects related to urinary stents. Sections within the work cover clinical and recent technological advancements in the field. Chapters feature detailed coverage of the different surgical, pharmacological and palliative treatments currently available. Insight is also given on current limitations of urinary stents and how these can be overcome by utilizing anti-biofilm coatings; new biomaterials, drug-eluting stents, and biodegradable stents. Therefore, enabling the reader to systematically gain a detailed understanding of the subject. Urinary Stents is a practical, multi-disciplinary focused resource on the complications and applications of ureteral, urethral and prostatic stents in day-to-day clinical practice. A vital read for all medical professionals and researchers who work in this area.